Influence of dendritic cells on corneal nerve morphological analysis and clinical relevance in chronic dry eye disease after femtosecond laser-assisted laser in situ keratomileusis - Liu, Yilin; Ma, Baikai; Zhao, Lu; Li, Hongshuo; Li, Wenlong; Sun, Zhengze; Duan, Hongyu; Zhao, Yitian; Qi, Hong (Frontiers in Medicine, 2025)
PurposeThis study aims to investigate the influence of dendritic cells (DCs) on corneal nerve morphology and the clinical significance in chronic Femtosecond Laser-Assisted Laser in Situ Keratomileusis (FS-LASIK) related dry eye disease (DED).MethodsThe cross-sectional study was conducted involving healthy control, DED without FS-LASIK group, and DED after FS-LASIK group. Clinical parameters such as ocular surface disease index (OSDI), fluorescein tear breakup time (FBUT), corneal fluorescein staining (CFS) scores, Schirmer I test (SIt), Cochet-Bonnet esthesiometer (C-BE) were recorded. DCs of in vivo confocal microscopy images were included or excluded during corneal nerve segmentation. Key morphological parameters, including corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), tortuosity, and box-count fractal dimension (Boxdim), were measured. The impact of DCs on nerve metrics and clinical parameters and the correlations between each other were assessed.ResultsThe significant reduce in key morphological parameters was observed after eliminating DCs. Significant differences of morphological parameters were observed in DED after FS-LASIK group compared with other two groups. With the increased presence of DCs density in DED especially in DED after FS-LASIK group, the presence of DCs introduced false positives in the correlation analysis of DCs density with corneal morphology in DED after FS-LASIK and in the correlation analysis of corneal morphology with clinical characteristics in DED without FS-LASIK.ConclusionThe presence of DCs introduces significant biases in the assessments of corneal nerve morphology, primarily false-positive results in DED especially chronic FS-LASIK related DED. Their exclusion improves the precision of nerve measurements, which may enhance the clinical evaluation of corneal nerve morphology. These findings highlight the importance of precise segmentation techniques to minimize DCs related interference in clinical practice.